A reproducible in vitro pollen germination medium for recalcitrant cereal rye pollen (Secale cereale L): Effect of tryptone - Jayaprakash, P.; Sheeba, D.; Vikas, V. K.; Sivasamy, M.; Kumar, Jagdish; Annapoorani, S.; Krishnan, Navaneetha (The Indian Journal of Genetics and Plant Breeding, 2017)
A reproducible in vitro pollen germination medium (PGM)for cereal rye is reported here using tryptone for the firsttime. Rye pollen is very difficult to germinate on nutrientmedium being trinucleate and is classified as recalcitrantpollen. This study addresses the possibility of testing theviability of rye pollen within short time (15-20 min) usingpollen germination medium (PGM). The viability of ryepollen was tested with FDA staining also. The results ofboth staining and in vitro pollen germination were foundcomparable. In this study, tryptone, a nitrogen source wasused in addition to essential sugar and inorganic salts.PGM used for rye consisted of 19% maltose, 13% polyethylene glycol 6000, 62.5 mgl-1 boric acid, 50 mgl-1tryptoneand 1% agar. During the flowering period, a pollen sterilityof 3-12% was recorded. The PGM showed >93% pollengermination with intact pollen tubes at 17Â±1oC and pH 6-7.This tool would be useful in many pollen biotechnologicalaspects such as pollen transformation, overcomingcrossability barriers especially in wheat x rye widehybridization etc.